PS02.001: IMPLICATIONS OF JEJEUNOSTOMY OMISSION IN COMBINATION WITH EARLY FEEDING IN A MINIMALLY INVASIVE ESOPHAGECTOMY COHORT. (14th September 2018) - Carroll, Paul; Allison, Frances; Yeung, Jonathan; Darling, Gail
Abstract: Background: Early oral feeding in esophagectomy is recognised as safe in esophagectomy. Typically, enteral feeding has been used in combination to avoid weight loss in the recovery period post surgery. Recently, avoidance of jejeunal feeding has been shown to be efficacious with respect to nutritional safety over one year post surgery. In Toronto, jejeunostomy insertion is routinely omitted in our minimally invasive esophagectomy practice. Methods: This study sought to determine the nutritional impact this practice has by determining the examining a retrospective cohort before and after the practice change in 2016. Only patients with complete weight measurement follow up to 1 year were incorporated. Data displayed as median and interquartile range (IQR). Results: The initial results analysis consists of a total of 63 patients (n = 38 with feeding Jej (FJ) and n = 25 without (NFJ). Median BMI at surgery was 26 kg/m2 (23.1–30.5) with no differences between the groups identified: FJ BMI 25.9 (23–29.4) vs NFJ 26.8(23.9–32.2). Length of stay was 10 days in both groups. At one year, BMI was 23.4 (20.6–26.0) with no difference between the groups, FJ 22.4 (20.6–25.9) vs 23.4 (20.9- 27.7), P  = 0.798. Median weight loss at 1 year was 11.2kg (9.1%). More weight loss was identified in the NFJ group in the 1 st month, 4kg (1.9–5.1) vs 7kg (4.5–10.4) ( P  = 0.035) but subsequent intervals demonstrated no significant difference. Readmissions within one year were higher in the FJ group (n = 10, of which 2 needed operative intervention for jejeunostomy site issues), as compared to a single admission in the NFJ group for a para-conduit hernia repair. Conclusion: Early commencement of oral nutrition in combination with the omission of feeding jejeunostomy insertion has no prolonged nutritional impact after the 1 st month. Overall, Body mass index is reduced in esophagectomy patients over the first year irrespective of feeding approach. Disclosure: All authors have declared no conflicts of interest.